2019
DOI: 10.1021/acs.cgd.8b01897
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometry Driven Ferromagnetism in Double Perovskite La2Ni1–xMn1+xO6 Insulating Thin Films

Abstract: In this work we report on the epitaxial growth of La 2 NiMnO 6 double perovskite thin films on top of (001) oriented SrTiO 3 substrates by RF magnetron sputtering. The influence of oxygen pressure (P O 2 ) and growth temperature on the microstructure, stoichiometry of the films, and magnetic and transport properties is thoroughly investigated. It is found that high oxygen pressure promotes the growth of stoichiometric films, with a Ni/Mn ratio almost equal to 1. However, these films exhibit poor ferromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
4
5
0
Order By: Relevance
“…The magnitudes of ρ 0 and T 0 were 4.83 × 10 −12 Ω m and 1.12 × 10 8 K, respectively. The T 0 value is in agreement with those observed for similar double perovskites [57,59]. The density of localized states N(E F ) at the Fermi level is related to T 0 as, T 0 = 24/[πK B N(E F )ξ 3 ], where ξ is the decay length and assumed to be nearly equal to the average distance between the neighboring Ni or Mn ions estimated from the Rietveld analysis.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The magnitudes of ρ 0 and T 0 were 4.83 × 10 −12 Ω m and 1.12 × 10 8 K, respectively. The T 0 value is in agreement with those observed for similar double perovskites [57,59]. The density of localized states N(E F ) at the Fermi level is related to T 0 as, T 0 = 24/[πK B N(E F )ξ 3 ], where ξ is the decay length and assumed to be nearly equal to the average distance between the neighboring Ni or Mn ions estimated from the Rietveld analysis.…”
Section: Resultssupporting
confidence: 85%
“…The temperature dependence of resistivity ρ(T ) of La 2 Ni 0.5 Mn 1.5 O 6 in the interval of 130-325 K is plotted in figure 9(a). With decreasing temperature, it increased, indicating the insulating behavior of the material in the entire temperature range [57,58]. The various conduction models such as Efros-Shklovskii Hopping (ESH), thermal activation (TA), and variable range hopping (VRH) were attempted to describe the transport mechanism in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…However, the problem of oxygen deficiency and/or preparation-induced defects for PLD-grown films probably still exist in order to obtain strong magnetic properties; for example, in LCMO films [31] a post-annealing in 500 mbar of oxygen at 700 • C was shown to be a necessary condition. Several reports on the growth of LCMO [32] and LNMO [33] films by rf-sputtering under pO 2 ~0.1-0.5 mbar also pointed out the importance of post-annealing in the improvement of oxygen stoichiometry and magnetism in these films. Truong et al [25] reported the influence of growth conditions (temperature/pO 2 ) on the Ni/Mn ordering, studied by Raman spectroscopy, in the PLDgrown LNMO(111)/STO(111)films.…”
Section: Cation Ordering In Thin Filmsmentioning
confidence: 99%
“…The saturation magnetization, Curie temperature, and evolution of other phases like spin glass in La 2 NiMnO 6 depend on the cation ordering and cation valences. The synthesis processes or conditions affect the cation order and valences [15,28,29]. The physical properties of La 2 NiMnO 6 can also be tuned by partial doping, such that it can be made applicable for a variety of spintronic applications.…”
Section: Introductionmentioning
confidence: 99%